Analisis Kestabilan Lereng Area Highwall Section B Tambang Batubara PT. Manggala Usaha Manunggal Jobsite Pt. Banjarsari Pribumi, Kecamatan Merapi Timur, Kabupaten Lahat, Sumatera Selatan - Ade Elsa Marini; Yoszi Mingsi Anaperta; Tri Gamela Saldy (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. — PT. Manggala Usaha Manunggal is a contractor company that trusted to do coal mining by PT. Banjarsari Pribumi in Merapi Timur, Lahat Regency, South Sumatera. PT. Manggala Usaha Manunggal using open pit mining method. At the crest area of highwall section B there is the pile of overburden materials. Slope stability analysis using the Monte Carlo probabilistic method, the factor of safety and probability of failure for the recommendation of slope geometry will be obtained using Bishop Simplified method. As the results are the result of slope stability analysis on highwall section B shown that there is no decrease in slope stability where the value of factor before and after being given additional load is the same, that is 3,017 and the probability of Failure is 0% .